Adsorption of orange 11 and amaranth by surfactant modified zeolite X : effect of surfactant loading - Alias Mohd. Yusof, 1960-, author; Rabi'atul 'Adawiyah Mohd. Shah, 1987-, author; Nik Ahmad Nizam Nik Malek, author; Nur Hidayani Shaffe, author; Noor Aini Abdul Rashid, author; Asian Conference on Analytical Science (ASIANALYSIS X) on SKAM 2.2 (10th: 2009: Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL